Composition, fluororesin sheet and method for producing the same
Patent Information
- Application Number
- JP2024124501
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-03-08
- Filing Date
- 2024-07-31
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing fluororesin compositions for high-frequency printed wiring boards fail to achieve low dielectric constant, low loss, and low thermal expansion, limiting their performance in high-frequency applications.
A fluororesin composition with a specific ratio of fluororesin to filler, characterized by a dielectric loss tangent of the filler measured at 10 GHz to surface area ratio of 0.00001 to 0.00035, using spherical silica particles with surface treatment to reduce polar functional groups, and a blend of 50% to 68% filler content by weight, ensuring low dielectric constant, low loss, and low thermal expansion.
The composition achieves a fluororesin sheet with excellent low dielectric constant, low loss, and low thermal expansion, suitable for high-frequency applications, maintaining stability across a wide temperature range and frequency spectrum.
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a composition, a fluororesin sheet, and a method for producing the same. [Background technology]
[0002] There is a demand for high-frequency printed wiring boards with low transmission loss. In such high-frequency printed wiring boards, the use of fluororesin films It is known that a fluorine resin containing a filler is used as a wiring board material (Patent Document 1, etc.). The use of fats is described in Patent Documents 2 and 3.
[0003] Furthermore, Patent Document 4 discloses a fluororesin composition in which spherical silica particles are blended with a fluororesin. Its use on circuit boards is disclosed. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication 2015-8260 [Patent Document 2] Japanese Patent Application Publication No. 63-259907 [Patent Document 3] Special table 2022-510017 [Patent Document 4] International Publication 2020 / 145133 Summary of the Invention [Problem to be solved by the invention]
[0005] The present disclosure relates to a fluororesin having excellent performance in terms of low dielectric constant, low loss, and low thermal expansion. The present invention provides a composition for obtaining a fluororesin sheet, a thin fluororesin sheet, and a method for producing the same. The purpose is to [Means for solving the problem]
[0006] The present disclosure relates to Fluorine resin and (Dielectric tangent of the filler measured at 10 GHz) / (surface area of the filler (m 2 / g) ratio The composition is characterized by containing a filler having a viscosity of 0.00001 to 0.00035. The fluororesin is preferably a polytetrafluoroethylene resin. The fluororesin is preferably non-melt moldable.
[0007] The polytetrafluoroethylene resin preferably has an SSG of 2.0 to 2.3. . The polytetrafluoroethylene resin preferably has a refractive index of 1.2 to 1.6. stomach. The above fluororesin preferably has a primary particle size of 0.05 to 10 μm. The fluororesin preferably has a volume-based cumulative 50% diameter of 0.05 to 40 μm.
[0008] The filler is preferably silica particles. The content of the filler in the total amount of the composition is preferably 50 wt % or more. The filler preferably has an average particle size of 0.5 to 250 μm. The filler is preferably one whose surface is coated with a silane coupling agent. It is. The composition preferably has a dielectric loss tangent value of 0.0015 or less at 10 GHz.
[0009] The present disclosure relates to a fluororesin and a filler having a dielectric loss tangent measured at 10 GHz / filler surface area. Area (m 2 / g)) of 0.00001 to 0.00035. The fluororesin sheet is also characterized in that The fluororesin sheet preferably has a thickness of 5 to 250 μm.
[0010] The present disclosure is characterized by having a process of mixing fluororesin particles and a filler to form a film. This also relates to a method for producing the above-mentioned fluororesin sheet. In the above manufacturing method, only the fluororesin particles and the inorganic filler are mixed, and other components are not added. It is preferable to form the film without any problem.
[0011] The present disclosure also relates to a copper clad laminate having a copper foil and the above-mentioned fluororesin film as essential layers. The present disclosure also relates to a circuit board comprising the above-mentioned copper clad laminate. Effect of the Invention
[0012] The fluororesin sheet obtained from the composition of the present disclosure has low dielectric constant, low loss, and low thermal expansion. In addition, the sheet can be made thinner. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The present disclosure will be described in detail below. Many studies have been conducted on compositions that contain fluororesins and fillers. In the field of high-frequency printed wiring boards, in recent years, there has been an increasing demand for low dielectric constant, low loss, and Such high level of low dielectric constant, low loss, and low expansion is required. There has not always been sufficient consideration given to obtaining the necessary information.
[0014] In the present disclosure, a fluororesin having unprecedentedly high levels of low dielectric constant, low loss, and low expansion is The object is to provide a composition for obtaining a sheet.
[0015] (Filler) The composition of the present disclosure contains a fluororesin and a filler, and the dielectric constant of the filler measured at 10 GHz is dissipation factor) / (surface area of filler (m 2 / g) ratio is 0.00035 to 0.00001 That is, the filler satisfies the above-mentioned specific parameters. The present invention is characterized by the use of the above.
[0016] The dielectric loss tangent of the filler is greatly affected by the polar functional groups on the surface. For example, in the case of silica, In this case, the amount of Si-OH groups on the surface affects the dielectric tangent. The greater the amount of -OH groups, the greater the dielectric tangent of the filler. Therefore, it is preferable to reduce the amount of Si--OH on the surface.
[0017] From this viewpoint, (dielectric tangent of the filler measured at 10 GHz) / (surface area of the filler) Product(m 2 / g) is an index showing the amount of surface polar functional groups per unit surface area of the filler. The present inventors have attempted to reduce the amount of such surface polar functional groups and to obtain a surface polar functional group having a molecular weight within the above-mentioned predetermined range. When used in the above conditions, this fluororesin sheet has excellent low dielectric constant, low loss, and low expansion. The present disclosure has been completed based on the discovery that the above-mentioned formula can be obtained.
[0018] (Dielectric tangent of the filler measured at 10 GHz) / (surface area of the filler (m 2 / g) ratio In order to obtain a filler having a viscosity within the above-mentioned range, the filler to be used is selected. In addition, it is necessary to perform a surface treatment. The polar functional groups present on the surface are reacted to reduce the amount of the polar functional groups, thereby Such surface treatments are described in more detail below.
[0019] (Dielectric tangent of the filler measured at 10 GHz) / (surface area of the filler (m 2 / g)) The upper limit is more preferably 0.00030, and even more preferably 0.00025. I wish.
[0020] In this disclosure, the dielectric loss tangent of the filler measured at 10 GHz is Using a network analyzer, filler powder samples are filled into a quartz tube and loaded into a resonator for measurement. The characteristics of the resonator (resonant frequency and Q value) were obtained before and after the sample was inserted, and the dielectric constant was calculated from the results. This measurement method is based on the Japanese Industrial Standard JIS2565 microwave ferrite core test. The test method was based on the standard, and measurements were performed in an environment with a room temperature of 25°C and a humidity of 40%.
[0021] In the present disclosure, the dielectric tangent of the filler measured at 10 GHz is not particularly limited. However, it is preferable that the value is 0.0015 or less. It is preferable that the loss of the grease sheet is low. It is more preferable that the ratio is 0.002, and further more preferable that the ratio is 0.002.
[0022] In the present disclosure, the surface area (m 2 / g) is not particularly limited, but may be 1 By setting it within the above range, the fluororesin sheet can achieve low loss and low This is preferable in terms of a good balance of linear expansion. The lower limit is more preferably 1.2. The upper limit is preferably 9, and more preferably 7. It is more preferable that:
[0023] In the present disclosure, the surface area (m 2 / g) is the specific surface area based on the BET method. The specific surface area measuring device is "Macsorb HM model-1208" (MA The measurement can be performed using a fluororesin sheet manufactured by CSORB Co., Ltd. When two or more fillers are used, the surface area measured for the entire mixture of fillers is It falls within the range mentioned above.
[0024] In the present disclosure, the filler preferably has an average particle size of 0.5 to 250 μm. The average particle size here is the D50 value measured by a laser analysis particle size distribution analyzer. If the average particle size is less than 0.5 μm, the filler will aggregate and the effect will not be sufficient. This is undesirable in that it cannot be
[0025] The filler that can be used in the present disclosure is not particularly limited, and may be, for example, aramid fiber, Polyphenyl ester, polyphenylene sulfide, polyimide, polyether ether One or more selected from the group consisting of polyketone, polyphenylene, polyamide, and wholly aromatic polyester resin Organic fillers, ceramics, talc, mica, aluminum oxide, zinc oxide, tin oxide , titanium oxide, silicon oxide, calcium carbonate, calcium oxide, magnesium oxide, titanium Potassium phosphate, glass fiber, glass fragments, glass beads, silicon carbide, calcium fluoride, nitrogen One selected from boron disulfide, barium sulfate, molybdenum disulfide and potassium carbonate whisker The inorganic fillers may be any of the above. This is also possible.
[0026] The shape of the filler is not particularly limited, but it is particularly preferred that the filler be spherical. If it is spherical, it is easier to process uniformly during drilling, and the specific surface area is small, so transmission loss is low. It is preferable because it is low.
[0027] Among these, it is particularly preferable to use silica, and it is preferable to use spherical silica particles. is most preferred.
[0028] The spherical silica particles refer to particles whose particle shape is close to a perfect sphere. The degree of shape is preferably 0.80 or more, more preferably 0.85 or more, and More preferably, the sphericity is 0.90 or more, and most preferably, 0.95 or more. From the area and perimeter of the observed particle, (sphericity) = {4π × (area) ÷ (perimeter) )2}. The closer it is to 1, the closer it is to a perfect sphere. 100 particles were measured using a spectrophotometer (Spectris Corporation: FPIA-3000). The average value determined is used.
[0029] The spherical silica particles used in the present disclosure have a D90 when integrating the volume from the smallest particle size. / D10 is 2 or more (preferably 2.3 or more, 2.5 or more), and D50 is 10 μm or less It is preferable that D90 / D50 is 1.5 or more (more preferable). It is preferable that the D50 / D10 ratio is 1.5 or more (more preferably, 1.6 or more). Furthermore, it is more preferable that D50 is 5 μm or less. Small spherical silica particles can be inserted into the gaps between the silica particles, improving filling properties. In particular, the particle size distribution is much smaller than the Gaussian curve. It is preferable that the frequency of the smaller particle size is high. It can be measured by a measuring device. In addition, since coarse particles make it difficult to make the sheet thin, It is preferable that coarse particles having the above particle size have been removed using a filter or the like.
[0030] The spherical silica particles preferably have a water absorption of 1.0% or less, and more preferably 0.5% or less. It is more preferable that the water absorption is based on the mass of the silica particles when dry. The dry sample was left at 40°C and 80% RH for 1 hour and then measured using the Karl Fischer moisture meter. The moisture produced by heating to 200°C is measured using a measuring device and calculated.
[0031] The spherical silica particles were prepared by heating a fluororesin sheet at 600°C for 30 minutes in an air atmosphere. The fluororesin is burned off by heating, and the spherical silica particles are taken out, and then the above-mentioned method is repeated. It is also possible to measure the above parameters using the same.
[0032] The silica particles are surface-treated. By previously performing the surface treatment, the silica It is possible to suppress particle aggregation and to satisfactorily disperse silica particles in a resin composition. In addition, the above (dielectric tangent of the filler measured at 10 GHz) / (surface area of the filler) (m 2 / g) can be set within a predetermined range.
[0033] The above surface treatment is based on the following formula: (Dielectric tangent of the filler measured at 10 GHz) / (Surface area of the filler ( m 2 In order to make the ratio of 0.1 to 0.2g / g within a predetermined range, the type of surface treatment agent and The amount of treatment can be appropriately selected.
[0034] The surface treatment is not particularly limited, and any known surface treatment may be used. Specifically, for example, epoxysilane, aminosilane, isosilane, etc. having a reactive functional group can be used. Cyanate silane, vinyl silane, acrylic silane, hydrophobic alkyl silane, phenyl Treatment with silane coupling agents such as silane and fluorinated alkylsilanes, plasma treatment , fluorination treatment, etc.
[0035] The silane coupling agent is, for example, γ-glycidoxypropyltriethoxysilane, β- Epoxy silanes such as (3,4-epoxycyclohexyl)ethyltrimethoxysilane, Aminopropyltriethoxysilane, N-phenylaminopropyltrimethoxysilane, etc. Aminosilanes, isocyanate silanes such as 3-isocyanatopropyltrimethoxysilane silanes such as vinyltrimethoxysilane, and acryloxytrimethoxysilane Examples include chlorsilane.
[0036] The spherical silica particles used are commercially available silica particles that satisfy the above-mentioned properties. As commercially available silica particles, for example, Denka fused silica FB grade ( Denka Fused Silica SFP Grade (Denka) Rika (manufactured by Tokuyama Corporation), high-purity synthetic spherical silica particles ADMAFINE (manufactured by A Domatechs), Admanano (Admatechs Co., Ltd.), AdmaFuse (AdmaFuse Co., Ltd.) (manufactured by Admatechs Co., Ltd.), etc.
[0037] (Dielectric tangent of the filler measured at 10 GHz) / (surface area of the filler (m 2 / g) value can be adjusted by the filler shape, filler size, whether or not surface treatment is performed, etc. More specifically, the spherical silica particles described above are of a predetermined size. It is preferable that the surface of the substrate is subjected to a surface treatment. The type of the compound also affects the above parameters. More specifically, aminopropyl trimethylsilyl Ethoxysilane, aminosilane, vinylsilane, hydrophobic alkylsilane, phenylsilane silane, 3-mercaptopropylsilane, 3-acryloxypropylsilane, 3-methacryloxypropylsilane p-Styrylsilane, p-Styrylsilane, Silylpropylsuccinic anhydride, 3-isocyanate Surface treatment with propylsilane, 2-(3,4-epoxycyclohexyl)ethylsilane, etc. It is particularly preferable to use a silane coupling agent for surface treatment. By applying the treatment, the polar functional groups present on the filler surface react, and the amount of the polar functional groups is reduced. Therefore, it has excellent electrical properties.
[0038] The filler is preferably contained in an amount of 50% by weight or more based on the weight of the sheet. By using this amount, it is possible to achieve low thermal expansion while maintaining a low dielectric constant and low loss. The blending amount is preferably 53% by weight or more, more preferably 56% by weight or more. The upper limit of the amount of the filler to be blended is not particularly limited, but , preferably 68% by weight or less, and more preferably 65% by weight or less.
[0039] (Fluorine resin) The composition of the present disclosure contains a fluororesin. The fluororesin has low dielectric properties. Therefore, it can be suitably used for the purpose of the present disclosure.
[0040] The fluororesin that can be used in the present disclosure is not particularly limited, but examples thereof include For example, polytetrafluoroethylene (PTFE), tetrafluoroethylene (TFE) / Hexafluoroethylene (Hexafluoroethylene) Hexafluoropropylene (HFP) copolymer (FEP), TFE / alkyl vinyl ether copolymer [PFA], TFE / HFP / alkyl vinyl ether copolymer [EPA], TFE / chlorotrifluoroethylene (CTFE) copolymer, TFE / ethylene copolymer [ETFE], polyvinylidene fluoride [PVdF], tetrafluoroethylene with molecular weight of 300,000 or less Ethylene [LMW-PTFE], etc. may be used alone or in combination. From the viewpoint of low dielectric properties, polytetrafluoroethylene resin (PTF E) is particularly preferred. PTFE is preferably one having fibrillation properties. PTFE with brilicity means PTFE that can be paste-extruded from unsintered polymer powder. Taste.
[0041] PTFE is modified polytetrafluoroethylene (hereinafter referred to as modified PTFE). Alternatively, it may be homopolytetrafluoroethylene (hereinafter referred to as homo PTFE). Alternatively, it may be a mixture of modified PTFE and homo-PTFE. The content of the modified PTFE in the polytetrafluoroethylene resin is set to a value that maintains good moldability of the polytetrafluoroethylene. From the viewpoint of the above, the content is preferably 10% by weight or more and 98% by weight or less, and more preferably 50% by weight or more and 95% by weight or less. The homo-PTFE is not particularly limited, and is described in Japanese Patent Application Laid-Open No. 53-1978. 60979, JP 57-135, JP 61-16907, JP 57-135, JP 61-16907, JP 62-104816, JP 62-190206, JP 63-13790 6, JP 2000-143727 A, JP 2002-201217 A, International Publication No. 2007 / 046345 Brochure, International Publication No. 2007 / 119829 Brochure, International Publication No. 2009 / 001894 Brochure, International Publication No. 2010 / 113950 brochure, International Publication No. 2013 / 027850 brochure, etc. Among them, the homo PTFE disclosed in JP-A-2003-163635 has high stretchability. 57-135, JP 63-137906 A, JP 2000-143727 A Publication No. 2002-201217, International Publication No. 2007 / 046345 Lett., International Publication No. 2007 / 119829, International Publication No. 2010 / 11 Homo PTFE as disclosed in the pamphlet No. 3950 is preferred.
[0042] Modified PTFE is a mixture of TFE and monomers other than TFE (hereinafter referred to as modified monomers). Modified PTFE consists of those that are uniformly modified by the modifying monomer, and those that are modified in the early stages of the polymerization reaction. Those modified at the beginning of the polymerization reaction, those modified at the end of the polymerization reaction, etc. The modified PTFE may be, but is not limited to, any of the following, within the range that does not significantly impair the properties of the TFE homopolymer: A TFE copolymer obtained by subjecting a small amount of a monomer other than TFE to polymerization together with TFE. The modified PTFE is preferably a polymer. , JP-A-61-16907, JP-A-62-104816, JP-A-62-19 0206 Publication, JP-A-64-1711, JP-A-2-261810, JP-A-Hei 11-240917, JP 11-240918, WO 2003 / 033555 Brochure, International Publication No. 2005 / 061567 Brochure, International Publication No. 2007 / 005361 Brochure, International Publication No. 2011 / 055824 Brochure, Country The one disclosed in the pamphlet of International Publication No. 2013 / 027850 can be suitably used. Among them, the cellulose acylates disclosed in JP-A-61-16907 and JP-A-62-10010 have high stretchability. 4816, JP 64-1711 A, JP 11-240917 A, International Publication No. Pamphlet No. 2003 / 033555, Pamphlet No. 2005 / 061567 , International Publication No. 2007 / 005361, International Publication No. 2011 / 055 Modified PTFE as disclosed in, for example, Pamphlet No. 824 is preferred.
[0043] Modified PTFE is a mixture of TFE units based on TFE and modified monomer units based on modified monomers. The modified monomer unit is a part of the molecular structure of the modified PTFE. The modified PTFE is a modified monomer unit that accounts for 0.00 of the total monomer units. The content is preferably 1 to 0.500% by weight, and more preferably 0.01 to 0.30% by weight. The total monomer units are the parts derived from all monomers in the molecular structure of the modified PTFE. minutes.
[0044] The modifying monomer is not particularly limited as long as it can be copolymerized with TFE. For example, Perfluoroolefins such as hexafluoropropylene (HFP); chlorotrifluoroethylene Chlorofluoroolefins such as ethylene (CTFE); trifluoroethylene, vinyl fluoride Hydrogen-containing fluoroolefins such as VDF; perfluorovinyl ethers; perfluorovinyl Examples of modified monoethylenes include fluoroalkyl ethylene (PFAE) and ethylene. The mer may be of one type or of multiple types.
[0045] The perfluorovinyl ether is not particularly limited, and may be, for example, a perfluorovinyl ether represented by the following general formula (1): Examples of the perfluorounsaturated compounds include CF2 = CF-ORf (1)
[0046] In the formula, Rf represents a perfluoro organic group.
[0047] In this specification, a perfluoro organic group is an organic group in which all hydrogen atoms bonded to carbon atoms are fluorine. The perfluoro organic group is an organic group having an ether oxygen atom. It's fine.
[0048] The perfluorovinyl ether is, for example, a compound represented by the above general formula (1), in which Rf is carbon. Perfluoro(alkyl vinyl ether), a perfluoroalkyl group with prime numbers of 1 to 10 The number of carbon atoms in the perfluoroalkyl group is preferably 1 to 5. The perfluoroalkyl group in PAVE is, for example, a perfluoromethyl group. , perfluoroethyl group, perfluoropropyl group, perfluorobutyl group, perfluoro Examples of PAVE include perfluoropentyl and perfluorohexyl groups. Perfluoropropyl vinyl ether (PPVE), perfluoromethyl vinyl ether (PMVE) ) is preferred.
[0049] The perfluoroalkylethylene (PFAE) is not particularly limited, and may be, for example, perfluoroalkylethylene. Perfluorobutylethylene (PFBE), perfluorohexylethylene (PFHE), etc. Can be obtained.
[0050] Modified monomers in modified PTFE include HFP, CTFE, VDF, PAVE, It is preferably at least one selected from the group consisting of PFAE and ethylene.
[0051] The fluororesin is preferably not melt-moldable. Even if heated above its melting point, the resin does not have sufficient fluidity, and the resin is generally This refers to a resin that cannot be molded by melt molding. PTFE is one example of this. do.
[0052] In the present disclosure, such a fluororesin that cannot be melt-molded is used, It is preferable that the fluororesin sheet is produced by a molding method that causes fibrillation. The molding method will be described later.
[0053] The above PTFE preferably has an SSG of 2.0 to 2.3. When used, it produces a PTFE membrane with high strength (cohesion and puncture strength per unit thickness). Since PTFE with a large molecular weight has a long molecular chain, the molecular chain is regular. In this case, the length of the amorphous part increases and the molecules become entangled. When the degree of entanglement between molecules is high, the PTFE membrane can withstand the addition of It is believed that the material is less likely to deform under high loads and exhibits excellent mechanical strength. The use of PTFE having a molecular weight tends to result in a PTFE membrane having a small average pore size.
[0054] The lower limit of the SSG is more preferably 2.05, and further preferably 2.1. The upper limit of the SSG is preferably 2.25, more preferably 2.2. Preferred.
[0055] Standard specific gravity (SSG) was measured by preparing samples according to ASTM D-4895-89. The specific gravity of the sample was measured by the water displacement method.
[0056] In this embodiment, the molecular weight (number average molecular weight) of the PTFE constituting the PTFE powder is, for example, For example, it is in the range of 2 to 12 million. The lower limit of the molecular weight of PTFE is 3 million. The upper limit of the molecular weight of PTFE is 10 million. Good too.
[0057] The number average molecular weight of PTFE can be measured using the standard specific gravity. There are two methods: one is to determine the specific gravity from the standard density, and the other is to measure the dynamic viscoelasticity when melted. The method uses samples molded in accordance with ASTM D-4895 98 and is The measurement can be carried out by the water displacement method according to JIS-792. , for example, S. Wu, Polymer Engineering & Science, 1988, Vol. 28, 538; This is explained in the same publication, 1989, Vol. 29, 273.
[0058] The refractive index of the above PTFE is preferably within the range of 1.2 to 1.6. By using a material having such a refractive index, it is preferable in terms of low dielectric constant. The range can be achieved by adjusting the polarizability or flexibility of the main chain. The lower limit of the refractive index is preferably 1.25, more preferably 1.30. The upper limit of the refractive index is 1.55. More preferably, it is 1.50, and most preferably, it is 1.45. is also preferred.
[0059] The refractive indexes are values measured using a refractometer (Abbemat 300).
[0060] In addition, the maximum endothermic peak temperature (crystalline melting point) of the above PTFE is preferably 340±7°C. I wish.
[0061] PTFE has a maximum peak temperature of 3.0 mm on the endothermic curve of the crystal melting curve measured by a differential scanning calorimeter. Low melting point PTFE below 38℃ and endothermic curve on crystal melting curve measured by differential scanning calorimeter The PTFE may have a high melting point with a maximum peak temperature of 342°C or higher.
[0062] Low melting point PTFE is a powder produced by emulsion polymerization, and the maximum endothermic peak temperature is It has a dielectric constant (ε) of 2.08 to 2.2 and a dielectric tangent (tan δ) of 1. .9×10 -4 ~4.0×10 -4 For example, Daikin Industries, Ltd. Polyflon fine powder F201, F203, F205, F301, F 302; Asahi Glass Co., Ltd. CD090, CD076; DuPont Co., Ltd. TF6C, TF6 2, TF40, etc.
[0063] The high melting point PTFE powder is also a powder produced by emulsion polymerization, and the maximum endothermic peak It has a low crystal melting point, a dielectric constant (ε) of 2.0 to 2.1, and a dielectric tangent (tan δ) of 1. .6×10 -4 ~2.2×10 -4The overall score is low. For example, Daikin Polyflon Fine Powder F104, F106 manufactured by Asahi Glass Co., Ltd.; CD manufactured by Asahi Glass Co., Ltd. 1, CD141, CD123; DuPont's TF6 and TF65.
[0064] The average particle size of the powder formed by secondary aggregation of both PTFE polymer particles is usually 250 to 2000 μm. In particular, the granulated powder obtained by granulation using a solvent is preferably the same as that obtained in the preliminary molding. This is preferable since it improves the flowability when filling the mold.
[0065] Powdered PTFE that satisfies the above-mentioned parameters can be obtained by conventional manufacturing methods. For example, International Publication No. 2015-080291 and International Publication No. 2012-0 The manufacturing method may be similar to that described in US Pat. No. 86710.
[0066] (composition) The composition of the present disclosure contains the above-mentioned filler and fluororesin. In addition, it may contain components other than the filler and fluororesin, or the filler and fluororesin may be used. The content of components other than filler and fluororesin may be 100%. is preferably 10% by weight or less.
[0067] The composition of the present disclosure has a filler content of 70% by weight or less based on the total amount of the composition. By including the filler in such a range, the linear expansion coefficient can be reduced, This is preferable in that it is easy to mold. The lower limit of the amount of the filler is not particularly limited. However, from the viewpoint of lowering the linear expansion coefficient, it is preferably 40% by weight. The upper limit is more preferably 68% by weight, and further preferably 65% by weight. The lower limit is more preferably 40% by weight, and even more preferably 45% by weight. preferable.
[0068] The composition of the present disclosure has a dielectric loss tangent of 0.0001 to 0.0015 at 10 GHz. By setting the thickness within this range, it is preferable that the loss is low. I wish.
[0069] Furthermore, the composition of the present disclosure has a dielectric tangent at 80 GHz of 0.0001 to 0. In such a wide frequency range, the dielectric loss tangent is low, and the loss Also, if the dielectric loss tangent at 80 GHz is low, the gain of the millimeter wave antenna is This is preferable because it improves the
[0070] (Fluororesin sheet) The fluororesin sheet of the present disclosure is a fluororesin and a filler (dielectric tangent measured at 10 GHz) ) / (surface area of filler (m 2 / g) ratio is 0.00001 to 0.00035 This includes the above. The fluororesin sheet of the present disclosure preferably has a thickness of less than 300 μm. Even if the card is thin, it can still achieve its purpose. Therefore, it is more preferable that the thickness is less than 200 μm, and further preferably less than 150 μm. In addition, if it is possible to process the thickness to 100 μm or less as necessary, it will be possible to use substrates of various thicknesses. This is preferable because it can be widely applied to the above-mentioned cases.
[0071] The fluororesin sheet of the present disclosure preferably has a linear expansion coefficient of 10 to 100 (ppm / °C). By keeping the thickness within the above range, a fluororesin sheet with low shrinkage and excellent dimensional stability can be obtained. The upper limit is more preferably 90, and further preferably 80. The lower limit is more preferably 12, and further preferably 15. The linear expansion coefficient in the specification is that of TMA-7100 (manufactured by Hitachi High-Tech Science Corporation) The TMA measurement was performed in tensile mode using a sample piece with a length of 20 mm and a width of 5 mm. Using a sheet cut to a thickness of 150 μm, the chuck distance was set to 10 mm, and the load was 49 mN The linear expansion coefficient was calculated from the displacement of the sample at -10 to 160°C with a heating rate of 2°C / min. The expansion rate was calculated.
[0072] The fluororesin sheet of the present disclosure has a rate of change in relative dielectric constant in the temperature range of -50 to 150°C of 0. It is preferably 0.025 or less, more preferably 0.023 or less, and even more preferably It is preferable that the value is 0.021 or less. If the value is within this range, the temperature dependence of the There is little change in electrical properties, and stable performance is obtained when used in high-frequency printed circuit boards. This is preferable in that
[0073] (Method of manufacturing fluororesin sheet) The fluororesin sheet of the present disclosure is formed by mixing the above-mentioned fluororesin particles and a filler to form a film. The manufacturing method is not limited to the above, but may be a paste extrusion method. This can be done by forming, powder rolling, etc.
[0074] As described above, the fluororesin used in the fluororesin sheet of the present disclosure is a melt-molding non-compatible fluororesin. It is preferable to use a fluororesin that is capable of withstanding the above-mentioned temperature. When forming it into a sheet, the powdered PTFE used as the raw material is fibrillated. It is preferable to form the molded product by this method.
[0075] The powdered PTFE preferably has a primary particle size of 0.05 to 10 μm. The use of such a material has the advantage of excellent moldability and dispersibility. The primary particle size here is a value measured in accordance with ASTM D 4895.
[0076] The powdered PTFE is a polytetrafluoroethylene resin having a secondary particle diameter of 500 μm or more. The fat content is preferably 50% by mass or more, and more preferably 80% by mass or more. By using PTFE with a particle size of 500 μm or more within the above range, high strength can be achieved. It has the advantage that it is possible to produce a composite sheet. PTF with a secondary particle size of 500 μm or more By using E, it is possible to obtain a composite sheet with lower resistance and excellent toughness.
[0077] The lower limit of the secondary particle size is preferably 300 μm, more preferably 350 μm. The upper limit of the secondary particle size is more preferably 700 μm or less. It is more preferable that the secondary particle size is 600 μm or less. The secondary particle size is determined, for example, by a sieving method. It is possible.
[0078] The powdered PTFE mentioned above allows the production of fluororesin sheets with higher strength and excellent homogeneity. Therefore, it is preferable that the average primary particle size is 50 nm or more. 0 nm or more, more preferably 150 nm or more, and particularly preferably 200 nm or more. The larger the average primary particle size of PTFE, the easier it is to use the powder for paste extrusion molding. When the paste is extruded, the increase in the pressure is suppressed, and the moldability is excellent. From the viewpoint of productivity in the polymerization process, it is preferable to use 350 nm. It is preferable that there is.
[0079] The above average primary particle diameter was measured using an aqueous dispersion of PTFE obtained by polymerization at a polymer concentration of Transmittance of 550 nm incident light per unit length of an aqueous dispersion adjusted to 0.22% by mass and the average primary particle size determined by measuring the unidirectional diameter in a transmission electron microscope photograph. A calibration curve is created, and the transmittance is measured for the aqueous dispersion to be measured. It can be determined based on this.
[0080] The PTFE used in the present disclosure may have a core-shell structure. As the PTFE, for example, a core of high molecular weight polytetrafluoroethylene is used in the particle. and lower molecular weight polytetrafluoroethylene or modified polytetrafluoroethylene. A modified polytetrafluoroethylene having a shell of fluororesin is also included. As the tetrafluoroethylene, for example, the tetrafluoroethylene described in JP-A-2005-527652 is used. Examples of the polytetrafluoroethylene include polytetrafluoroethylene.
[0081] The specific methods of paste extrusion molding and powder rolling molding are not particularly limited, but are as follows: The general method is described below.
[0082] (Paste extrusion molding) The method for producing the sheet is to extrude PTFE powder obtained using a hydrocarbon surfactant. (1a) mixing the mixture with an auxiliary agent; and (1b) paste extrusion molding the mixture. A step (1c) of rolling the extrudate obtained by extrusion molding, and a step (1d) of drying the rolled sheet. and (1e) a step of calcining the dried sheet to obtain a molded product. The paste extrusion molding is carried out by adding conventionally known additives such as pigments and fillers to the PTFE powder. It can also be done.
[0083] The extrusion aid is not particularly limited, and generally known extrusion aids can be used. For example, hydrocarbons Examples of the oil include crude oil.
[0084] (Powder rolling molding) The sheet can also be formed by powder rolling molding. By applying shear force to the fiber, it is fibrillated and formed into a sheet. Thereafter, a step of sintering the mixture to obtain a molded body may be included. More specifically, A step (1) of applying a shear force to a raw material composition containing a fluororesin and a filler while mixing the raw material composition. A step (2) of forming the mixture obtained by the step (1) into a bulk form; and A step (3) of rolling the bulk mixture obtained in the step (2) into a sheet. It should be noted that the powder can be obtained by the above-mentioned powder rolling molding. When forming a composite material, it is preferable to mix only fluororesin particles and inorganic filler and mold the mixture. stomach.
[0085] (Laminate) The sheet-shaped resin composition of the present disclosure can be used as a sheet for printed wiring boards by stacking it with other substrates. It can be used in layers.
[0086] The present disclosure is characterized in that a copper foil is bonded to one or both sides of the above-mentioned fluororesin film. As described above, the film containing the fluororesin of the present disclosure is a copper clad laminate. Since the present invention can be particularly suitably used in applications involving printed wiring boards, It can be suitably used as a copper clad laminate.
[0087] The copper foil preferably has an Rz of 1.6 μm or less. The composition also has excellent adhesion to copper foil with a high smoothness of Rz 1.6 μm or less. Furthermore, the copper foil has a thickness of at least 1.6 μm or less on the surface that is bonded to the above-mentioned fluororesin film. The other aspect does not particularly limit the Rz value. The above Rz is the highest The sum of the maximum peak height (Rp) and the maximum valley depth (Rv) of the The surface roughness is the ten-point average roughness as defined in JIS-B0601. The Rz was measured with a surface roughness meter (product name: Surfcom 470A, Tokyo Seiki) with a measurement length of 4 mm. The values were measured using a meter (manufactured by the company).
[0088] The thickness of the copper foil is not particularly limited, but is preferably in the range of 1 to 100 μm. It is more preferable that the thickness is within the range of 5 to 50 μm, and further more preferable that the thickness is within the range of 9 to 35 μm.
[0089] The copper foil is not particularly limited, and specific examples thereof include rolled copper foil and electrolytic copper foil. Some examples include:
[0090] There are no particular limitations on the copper foil with a Rz of 1.6 μm or less, and commercially available products can be used. Commercially available copper foils with Rz of 1.6 μm or less include electrolytic copper foil CF-T9DA-SV- 18 (thickness 18 μm / Rz 0.85 μm) (manufactured by Fukuda Metal Foil & Powder Co., Ltd.) This can be done.
[0091] The copper foil is surface-treated to increase the adhesive strength with the fluororesin film of the present disclosure. It may also be something like that.
[0092] The surface treatment is not particularly limited, but may be a silane coupling treatment, a plasma treatment, a corona treatment, or the like. The reactive functional groups of silane coupling agents are: Although not particularly limited, from the viewpoint of adhesion to a resin substrate, an amino group, a (meth)acrylic At least one selected from the group consisting of a mercapto group, an epoxy group, and a phenyl group is at the terminal. The hydrolyzable group is not particularly limited, but may be a methoxy group or an ethoxy group. The copper foil used in the present disclosure has an anti-rust layer (chromate, etc.) The material may have a heat-resistant layer or the like formed thereon.
[0093] The surface-treated copper foil having a surface-treated layer with a silane compound on the copper foil surface is The method comprises preparing a solution containing the compound, and then surface treating the copper foil with the solution. This can be done.
[0094] The copper foil has a roughening treatment layer on the surface from the viewpoint of improving adhesion to a resin substrate. It may also be something. In addition, if there is a risk that the roughening treatment may deteriorate the performance required in the present disclosure, it may be omitted. Depending on the situation, the amount of roughening particles electrodeposited on the copper foil surface may be reduced, or no roughening treatment may be performed. It can also be done.
[0095] Between the copper foil and the surface treatment layer, a heat-resistant treatment layer and a rust-proof treatment layer are placed to improve various properties. and a chromate treatment layer. The layer may be a single layer or multiple layers.
[0096] The copper clad laminate of the present disclosure further comprises layers other than the copper foil and the fluororesin film. It is also possible. The layers other than the copper foil and fluororesin film are polyimide and modified polyimide. , liquid crystal polymer, polyphenylene sulfide, cycloolefin polymer, polystyrene Epoxy resin, bismaleimide, polyphenylene oxide, modified polyphenylene At least one selected from the group consisting of polyphenylene ether, polyphenylene ether, and polybutadiene. It is preferable that the number of the amines is at least one.
[0097] The layers other than the copper foil and the fluororesin film may be made of the above-mentioned resins. There is no particular limitation. In addition, the layers other than the copper foil and the fluororesin film have a thickness of 12 It is preferable that it is in the range of 0.5 to 260 μm.
[0098] In the copper-clad laminate of the present disclosure, the copper layer may be formed on one or both sides of the roll film. The copper layer can be formed by laminating (adhering) copper foil to the surface of a roll film. The copper foil is laminated by a hot press method. The heat press temperature is between the melting point of the dielectric film -150°C and the melting point of the dielectric film. +40°C. The heat press time is, for example, 1 to 30 minutes. The pressure of the heat press is, It can be produced by a method of 0.1 to 10 MPa.
[0099] The copper clad laminate of the present disclosure is not particularly limited in its application, and is used as a circuit board. A printed circuit board is a device that electrically connects electronic components such as semiconductors and capacitor chips while The plate-shaped component is to be placed and fixed in the space provided by the copper clad laminate. There are no particular restrictions on the structure of the printed circuit board. The printed circuit board can be a rigid board, a flexible board, The printed circuit board can be either a single-sided, board, or double-sided. The substrate may be a multi-layer substrate (e.g., a pulled-up substrate). In particular, a flexible substrate may be used. It can be used effectively for high frequency applications, particularly for 10 GHz and above. The substrate can be suitably used as a support substrate.
[0100] The circuit board is not particularly limited, and the above-mentioned copper-clad laminate can be used to form the circuit board by a general method. It can be manufactured by the above method.
[0101] The laminate for a circuit board has a copper foil layer and the above-mentioned fluororesin film and base material layer. The substrate layer is not particularly limited, but may be made of glass fiber. It is preferable that the sheet has a fabric layer and a resin film layer.
[0102] The glass fiber fabric layer is a layer made of glass cloth, glass nonwoven fabric, or the like. The glass cloth can be commercially available, and silica is used to enhance the compatibility with fluororesin. The glass cloth is preferably treated with a coupling agent. , C glass, A glass, S glass, D glass, NE glass, low dielectric constant glass, etc. However, E glass, S glass, and NE glass are preferred because they are readily available. The weaving method may be plain weave or twill weave. The thickness of the glass cloth is usually 5 to 90 μm. The thickness is preferably 10 to 75 μm, but it should be thinner than the fluororesin film used. It is preferable that
[0103] The laminate may also be one in which a glass nonwoven fabric is used as a fabric layer made of glass fibers. Glass nonwoven fabric is a material made by binding short glass fibers with a small amount of binder compound (resin or inorganic). The glass fibers are bonded together with a binder compound or are entangled without the use of a binder compound. The shape is maintained by the above-mentioned process, and commercially available glass short fibers can be used. The diameter of the fiber is preferably 0.5 to 30 μm, and the fiber length is preferably 5 to 30 mm. Specific examples of binder compounds include epoxy resins, acrylic resins, cellulose, and polyvinyl chloride. Examples of binders include vinyl alcohol, resins such as fluororesins, and inorganic substances such as silica compounds. The amount of the dye compound used is usually 3 to 15 mass % based on the weight of the short glass fibers. Materials include E glass, C glass, A glass, S glass, D glass, NE glass, low dielectric The thickness of the glass nonwoven fabric is usually 50 μm to 1000 μm. The thickness of the glass nonwoven fabric in the present application is preferably 100 to 900 μm. In accordance with JIS P8118:1998, digital gauge DG-925 manufactured by Ono Sokki Co., Ltd. (Weight: 110 grams, surface diameter: 10 mm) In order to improve compatibility, the glass nonwoven fabric may be treated with a silane coupling agent.
[0104] Many nonwoven glass fabrics have a very high porosity of over 80%, so they are made of fluororesin. It is preferable to use a material thicker than the above and compress it by pressure before use.
[0105] The glass fiber fabric layer is a layer in which a glass cloth and a glass nonwoven fabric are laminated. This allows the properties of each to be combined to obtain suitable properties. . The glass fiber fabric layer may be in the form of a prepreg impregnated with a resin.
[0106] The laminate has a glass fiber fabric layer and a fluororesin film bonded at the interface. The glass fiber fabric layer is often partially or entirely impregnated with a fluororesin film. It may be possible. Furthermore, a prepreg was produced by impregnating a fabric made of glass fiber with a fluororesin composition. The prepreg thus obtained may further include the fluorine-containing polymer of the present disclosure. In this case, the resin film used for preparing the prepreg may be laminated. The fluororesin composition to be used is not particularly limited, and the fluororesin film of the present disclosure may be can also be used.
[0107] The resin film used as the base layer may be a heat-resistant resin film, a thermosetting resin film, or the like. The heat-resistant resin film is preferably a polyimide or a modified polyimide. , liquid crystal polymers, polyphenylene sulfide, etc. , epoxy resin, bismaleimide, polyphenylene oxide, modified polyphenylene ether Examples of suitable terpolymers include polyphenylene ether, polyphenylene ether, and polybutadiene. The heat-resistant resin film and the thermosetting resin film may contain reinforcing fibers. The fiber is not particularly limited, but for example, glass cloth, particularly low dielectric type, is preferred. It is nice. Dielectric properties, linear expansion coefficient, water absorption rate, etc. of heat-resistant resin film and thermosetting resin film The properties are not particularly limited, but for example, the dielectric constant at 20 GHz is preferably 3.8 or less. The dielectric constant at 20 GHz is preferably 3.4 or less, more preferably 3.0 or less. The inference is preferably 0.0030 or less, more preferably 0.0025 or less, and more preferably 0.0020 or less. The linear expansion coefficient is preferably 100 ppm / °C or less, more preferably 70 ppm / °C or less. More preferably, the water absorption is 40 ppm / ° C. or less, and even more preferably, the water absorption is 1.0% or less. , 0.5% or less is more preferable, and 0.1% or less is even more preferable. EXAMPLES
[0108] The present disclosure will be specifically described below based on examples. Unless otherwise specified, "parts" and "%" represent "parts by mass" and "% by mass", respectively.
[0109] In the following examples and comparative examples, the following silicas were used: [Table 1] In the table, ZA-30 Phenyl+Amino is phenyltrimethoxysilane and aminoethylamine. It is a 9:1 mixture of propyltrimethoxysilane and propyltrimethoxysilane.
[0110] The evaluation of each sample in Table 1 above was carried out based on the following methods. [Df (dielectric tangent) of filler] The dielectric loss tangent of the filler measured at 10 GHz was measured using a cylindrical cavity resonator and a network analyzer. The filler powder sample was filled into a quartz tube and then loaded into the resonator for measurement. The characteristics of the front and rear resonators (resonant frequency and Q value) were obtained, and the dielectric tangent was calculated from the results. This assumed method complies with the Japanese Industrial Standard JIS2565 Microwave Ferrite Core Test Method.
[0111] [D50] The measurement was performed using a laser analysis particle size distribution analyzer.
[0112] [Specific surface area of filler] The value is based on the BET method. The specific surface area is measured by the Macsorb HM mode Measurements were performed using a 30-μm LC-1208 (MACSORB Corporation).
[0113] Example 1 Sheet manufacturing method 1 (paste extrusion molding) PTFE powder (average particle size: 500 μm, apparent density: 460 g / L, standard ratio: 1.0 g / L) was used in the ratio shown in Table 1. The specified amounts of cellulose acetate (weight: 2.17) and silica were weighed and mixed in a mixer in the presence of dry ice. The temperature during the meeting was below -10℃. Oil (IP Solvent 2028) was added at 18 to 23 wt% to the obtained mixed powder, and the mixture was mixed. It was then aged for about 5 hours. The aged composition was preformed under a pressure of 3 MPa, and the preformed compact was heated at 40°C, 50°C, and The extrusion was performed at a rate of 1 mm / min to obtain an extrusion sample. The extrusion sample was rolled using two rolls. A sample with a film thickness of 125 μm was obtained, dried at 200° C. for 2 hours, and baked at 360° C. for 15 minutes. The pressure of the two rolls was then adjusted to create a sample with a film thickness of 30 μm. The specimens were then inspected for the presence or absence of holes or tears.
[0114] Each of the obtained samples was evaluated based on the following criteria. [Sheet Df] Using a split cylinder type dielectric constant / dielectric loss tangent measuring device (manufactured by EM Lab), , and Df was measured at 10 GHz and 80 GHz.
[0115] [Linear expansion coefficient] The TMA measurement was performed using a TMA-7100 (Hitachi High-Tech Science Corporation). The test was performed using a sheet cut into a sample piece measuring 20 mm in length, 5 mm in width, and 150 μm in thickness. Using a chuck, the distance between the chucks was set to 10 mm, and a load of 49 mN was applied at a temperature increase rate of 2 The linear expansion coefficient was calculated from the displacement of the sample at 0 to 150°C per minute.
[0116] [30μm thin film] The composition shown in Table 2 below is PTFE / silica = 40 / 60, and the thickness is 30 μm. Those in which a film could be formed without holes or tears were marked with an ◯, and those in which a film could not be formed were marked with an ×. The results are shown in Table 2.
[0117] [Table 2]
[0118] From the above results, the fluororesin sheet of the present disclosure has low dielectric constant, low loss, and low thermal expansion. In addition, the PTFE / silica of Example 8 (mass ratio: 40 / 60) has excellent performance. Df at 80GHz is 0.0008, and it has excellent performance even at 80GHz. It is.
[0119] In the above Examples 1 and 8, the sheet having PTFE / silica=40 / 60 was subjected to the following Based on this method, the rate of change in the relative dielectric constant was measured in the temperature range of -50 to 150°C. The results are shown in Table 1. Shown in 3.
[0120] (Method for measuring the rate of change in dielectric constant in the temperature range of -50 to 150°C) Using a split cylinder type dielectric constant / dielectric loss tangent measuring device (EM Lab), The Dk at 10 GHz was measured at 10°C intervals from 10°C to 150°C. The rate of change from -50°C to 150°C was calculated from the difference between the maximum and minimum measured Dk values.
[0121] [Table 3]
[0122] From the results in Table 3, the fluororesin sheet of the present disclosure has a relative dielectric constant in the temperature range of -50 to 150°C. It is clear that the rate of change is small. [Industrial Applicability]
[0123] The fluororesin sheet of the present disclosure can be particularly suitably used for high-frequency printed circuit boards. .
Claims
1. Fluorine resin and (Dielectric tangent of the filler measured at 10 GHz) / (surface area of the filler (m 2 / g) of 0.00001 to 0.00035; The filler has a dielectric tangent value of 0.0015 or less at 10 GHz; The rate of change in dielectric constant in the temperature range of -50 to 150°C is 0.025 or less. A composition comprising:
2. 2. The composition according to claim 1, wherein the fluororesin is a polytetrafluoroethylene resin.
3. 3. The composition according to claim 1, wherein the fluororesin is not melt-moldable.
4. The composition according to claim 2, wherein the polytetrafluoroethylene resin has an SSG of 2.0 to 2.
3.
5. 3. The composition according to claim 2, wherein the polytetrafluoroethylene resin has a refractive index of 1.2 to 1.
6.
6. 3. The composition according to claim 1, wherein the fluororesin has a primary particle size of 0.05 to 10 μm.
7. 3. The composition according to claim 1, wherein the fluororesin has a volume-based cumulative 50% diameter of 0.05 to 40 μm.
8. 3. The composition according to claim 1, wherein the filler is silica particles.
9. 3. The composition according to claim 1, wherein the content of the filler is 50 wt % or more based on the total amount of the composition.
10. 3. The composition according to claim 1, wherein the filler has an average particle size of 0.5 to 250 μm.
11. 3. The composition according to claim 1, wherein the filler has a surface coated with a silane coupling agent.
12. 3. The composition according to claim 1, having a dielectric tangent value of 0.0015 or less at 10 GHz.
13. Fluorine resin and (Dielectric tangent of the filler measured at 10 GHz) / (surface area of the filler (m 2 / g) of 0.00001 to 0.00035; The filler has a dielectric tangent value of 0.0015 or less at 10 GHz; The rate of change in dielectric constant in the temperature range of -50 to 150°C is 0.025 or less. A fluororesin sheet comprising a composition.
14. The fluororesin sheet according to claim 13, which has a thickness of 5 to 250 μm.
15. 15. The method for producing a fluororesin sheet according to claim 13, further comprising a step of mixing the fluororesin particles and a filler to form a film.
16. The method for producing a sheet-shaped composition according to claim 15, characterized in that a film is formed by mixing only the fluororesin particles and the inorganic filler without adding any other components.
17. A copper clad laminate comprising a copper foil and the fluororesin sheet according to claim 13 or 14 as essential layers.
18. A circuit board comprising the copper clad laminate according to claim 17.
